Trouble with working women - Lloyd-Davies, Fiona; Steele, Ben; British Broadcasting Corporation (Australia : BBC Productions, 2009)
Why are women's career prospects consistently less bright than those of their male counterparts? This provocative two-part series searches for insights into that question as BBC news personalities Sophie Raworth and Justin Rowlatt explore the so-called trouble with working women
Episode 1. Why can't a women suceed like a man - Episode 2. Why can't women earn as much as man
Title from title screen
Executive producer, Samantha Anstiss
Presenters: Sophie Raworth, Justin Rowlatt
DVD format
Keywords: Women -- Employment; Sex discrimination in employment; Equal pay for equal work